Bougainvillea Festival 2013 - Dutt, Som (Indian Horticulture, 2019)
THE Bougainvillea Society of India has organised a two-day Bougainvillea Festival from 23 to 24 March 2013, at the Budha Jayanti Park (CPWD), Ridge Road, New Delhi, a famous Japanese Style Garden of Delhi. The show was inaugurated by Hon'ble Dr Sudhir Krishna, Secretary, Ministry of Urban Development on 23 March 2013. Approximately 25 exhibitors participated in the show and displayed their exhibits and products. Around 50,000 visitors visited the show in additions to staff of horticulture department of Delhi and NCR. Some visitors outside Delhi also visited.